Informação e segurança pública: modelo de banco de dados para a gestão de informações em Moçambique - Nhacuongue, Januário Albino [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The current state of the network society shapes the processes of production, preservation and flow of information through the application of information technology and communication (ICT). This scenario driven by the use of digital information environments, specifically the Internet, reign new reflections on the prevailing level of any social actor on the potential strategic use of ICTs towards the revitalization of internal processes with a view to inclusion in the information society. E-commerce and publishing on-line public services that have been adopted by most organizations are clear examples of technologies that provide gains for development in all political, social and economic dimensions. In this process there is a dual need, both in the architecture of digital information environments for greater usability and accessibility, as the improvement in digital repositories to ensure the retrieval of information preserved for use and re-use. The Police of the Republic of Mozambique (PRM) is a service of public nature, especially public safety, democratic legality and rights of citizens is limited in this specimen. Thus, the study aimed to explore the potential of creating the database (DB) and the digital information environment for managing information about public security in Mozambique for the part of the PRM. To this end, we adopted the case study to obtain data with greater detail and to consider other aspects not previously covered by the research. The data collection among various techniques, including participant observation during the experience in organizing guided the research work, whose results turn out to be extremely important in that, besides stimulating the production of information in the area, will ensure the mechanisms for collection, organization, storage and information retrieval, making flexible the processing for rapid decisions in response to collective needs

O atual estágio da sociedade em rede modela os processos de produção, preservação e fluxo de informações através da aplicação das tecnologias da informação e comunicação (TIC). Este cenário impulsionado pelo uso de ambientes informacionais digitais, especificamente a Internet, impera novas reflexões no nível de qualquer ator social sobre as potencialidades do uso estratégico das TIC em prol da revitalização dos processos internos, com vista à inserção na sociedade de informação. O comércio eletrônico e a publicação de serviços públicos on-line que vêm sendo adotados pela maioria das organizações são exemplos elucidativos dos ganhos que as tecnologias proporcionam para o desenvolvimento em todas as dimensões políticas, sociais e econômicas. Neste processo observa-se uma dual necessidade, tanto na arquitetura dos ambientes informacionais digitais para uma maior usabilidade e acessibilidade, como no aperfeiçoamento dos repositórios digitais de modo a garantir a recuperação das informações preservadas para o uso e re-uso. A Polícia da República de Moçambique (PRM) é uma organização de prestação de serviços de natureza público, mormente a segurança pública, defesa da legalidade democrática e dos direitos dos cidadãos que se circunscreve neste espécime. Deste modo, o estudo visa explorar as potencialidades da criação do banco de dados (BD) e do ambiente informacional digital para a gestão de informações sobre a segurança pública em Moçambique pela parte da PRM. Para tal, adota-se o estudo de caso para obter dados com maior nível de detalhamento e ponderar outros aspectos não previstos previamente pela pesquisa. A coleta de dados, entre diversas técnicas, através da observação participante durante a experiência na organização norteou o trabalho de pesquisa, cujos resultados revelam-se de suma importância na medida...
Keywords: Tecnologia da informação; Sistema de informação gerencial; Banco de dados - Gerencia; Modelagem de dados; Segurança pública - Moçambique; Information and Technology; Database; Data modeling; Digital information environment; Information management; Public safety